New insights into TB physiology suggest untapped therapeutic opportunities. Issue 1 (March 2015) - Baer, Christina E.; Rubin, Eric J.; Sassetti, Christopher M.
Summary: The current regimens used to treat tuberculosis are largely comprised of serendipitously discovered drugs that are combined based on clinical experience. Despite curing millions, these drug regimens are limited by the long course of therapy, the emergence of resistance, and the persistent tissue damage that remains after treatment. The last two decades have produced only a single new drug but have represented a renaissance in our understanding of the physiology of tuberculosis infection. The advent of mycobacterial genetics, sophisticated immunological methods, and imaging technologies have transformed our understanding of bacterial physiology as well as the contribution of the host response to disease outcome. Specific alterations in bacterial metabolism, heterogeneity in bacterial state, and drug penetration all limit the effectiveness of antimicrobial therapy. This review summarizes these new biological insights and discusses strategies to exploit them for the rational development of more effective therapeutics. Three general strategies are discussed. First, our emerging insight into bacterial physiology suggests new pathways that might be targeted to accelerate therapy. Second, we explore whether the concept of genetic synergy can be used to design effective combination therapies. Finally, we outline possible approaches to modulate the host response to accentuate antibiotic efficacy. These biology‐driven strategies promise to produce more effective therapies.